2020
DOI: 10.1002/hipo.23250
|View full text |Cite
|
Sign up to set email alerts
|

Spatial encoding in dorsomedial prefrontal cortex and hippocampus is related during deliberation

Abstract: Deliberation is thought to involve the internal simulation of the outcomes of candidate actions, the valuation of those outcomes, and the selection of the actions with the highest expected value. While it is known that deliberation involves prefrontal cortical areas, specifically the dorsomedial prefrontal cortex (dmPFC), as well as the hippocampus (HPC) and other brain regions, how these areas process prospective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 97 publications
6
19
0
Order By: Relevance
“…The central role of the hippocampus for orchestrating goal-oriented behavior is further suggested by its involvement in “vicarious trial-and-error” behavior [ 138 ], as well as by the centrality of theta rhythms for intentional control [ 126 , 131 , 139 , 140 ]. Additional supporting evidence can be found in hippocampally-mediated orchestration of counterfactual inferences in other domains, ranging from predictive information over likely trajectories for locomoting rodents [ 141 , 142 ] to the simulation of alternative perspectives by imagining humans [ 143 , 144 ].…”
Section: From Action To Attention and Back Againmentioning
confidence: 98%
“…The central role of the hippocampus for orchestrating goal-oriented behavior is further suggested by its involvement in “vicarious trial-and-error” behavior [ 138 ], as well as by the centrality of theta rhythms for intentional control [ 126 , 131 , 139 , 140 ]. Additional supporting evidence can be found in hippocampally-mediated orchestration of counterfactual inferences in other domains, ranging from predictive information over likely trajectories for locomoting rodents [ 141 , 142 ] to the simulation of alternative perspectives by imagining humans [ 143 , 144 ].…”
Section: From Action To Attention and Back Againmentioning
confidence: 98%
“…Theta oscillations are prominent in CA1 during navigation, and CA1 cell assemblies are organized into theta sequences within single oscillation cycles. While it is not known whether ordered sequences of PFC cells occur during hippocampal theta oscillations, previous studies have shown that PFC cells phase-lock and phase-precess (i.e., spikes of a cell occur at progressively earlier theta phases as an animal move through its spatial field) to hippocampal theta oscillations (Jadhav et al, 2016;Jones and Wilson, 2005a;Siapas et al, 2005;Sigurdsson et al, 2010); further, theta-frequency synchrony and coherent spatial coding between the hippocampus and PFC is prominent during memory-guided navigation (Benchenane et al, 2010;Gordon, 2011;Hasz and Redish, 2020;Jones and Wilson, 2005b;Sigurdsson et al, 2010;Zielinski et al, 2019).…”
Section: Fast Theta Sequences In Ca1 and Pfcmentioning
confidence: 99%
“…In our opinion, however, it is more likely that examining HPC interactions with other areas, such as the medial prefrontal cortex (mPFC). (Brown et al, 2016;Voss and Cohen, 2017;Schmidt et al, 2019;Hasz and Redish, 2020;Kidder et al, 2021) (Jones and Wilson, 2005;Benchenane et al, 2010), suggestive of cross-regional communication (Fries, 2005(Fries, , 2015. Finally, experiments using optogenetics to perturb the mPFC in a taskepoch-specific manner during the SDA task showed that stimulation decreased the proportion of VTEs rats engaged in, with a trend toward choice epoch mPFC disruption having a greater effect than stimulation in other epochs (Kidder et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
“…We suspect part of the reason they have not received more attention is that VTE trajectories can be highly variable, which makes it difficult to identify them algorithmically (Goss and Wischner, 1956). The Redish lab has proposed the IdPhi metric, which quantifies changes in heading angles as rats traverse choice points, for identifying VTEs (Papale et al, 2012(Papale et al, , 2016Redish, 2016;Redish, 2016, 2018;Schmidt et al, 2019;Hasz and Redish, 2020). While successful in their hands, IdPhi, admittedly, "does not provide a sharp boundary between VTE and not" (Papale et al, 2016), Supplemental Material: Experimental Procedures).…”
Section: Background and Introductionmentioning
confidence: 99%